Potential risk factors of pediatric acute respiratory distress syndrome in sepsis - Kezia Theofani Saragih; Ririe Fachrina Malisie; Rini Savitri Daulay; Bobby Ramses Erguna Sitepu (Paediatrica Indonesiana, 2024)
Background Sepsis in children is characterized by a dysregulated host response to infection and life-threatening organ dysfunction. Pediatric acute respiratory distress syndrome (PARDS) is a severe complication of sepsis. Several known risk factors of PARDS are immunodeficiency, obesity, source of infection, and genetic factors.